GeSnOI mid-infrared laser technology - Binbin Wang (Nature Publishing Group, 2021)
Abstract GeSn alloys are promising materials for CMOS-compatible mid-infrared lasers manufacturing. Indeed, Sn alloying and tensile strain can transform them into direct bandgap semiconductors. This growing laser technology however suffers from a number of limitations, such as poor optical confinement, lack of strain, thermal, and defects management, all of which are poorly discussed in the literature. Herein, a specific GeSn-on-insulator (GeSnOI) stack using stressor layers as dielectric optical claddings is demonstrated to be suitable for a monolithically integration of planar Group-IV semiconductor lasers on a versatile photonic platform for the near- and mid-infrared spectral range. Microdisk-shape resonators on mesa structures were fabricated from GeSnOI, after bonding a Ge0.9Sn0.1 alloy layer grown on a Ge strain-relaxed-buffer, itself on a Si(001) substrate. The GeSnOI microdisk mesas exhibited significantly improved optical gain as compared to that of conventional suspended microdisk resonators formed from the as-grown layer. We further show enhanced vertical out-coupling of the disk whispering gallery mode in-plane radiation, with up to 30% vertical out-coupling efficiency. As a result, the GeSnOI approach can be a valuable asset in the development of silicon-based mid-infrared photonics that combine integrated sources in a photonic platform with complex lightwave engineering.